PERANCANGAN SISTEM INFORMASI KINERJA KARYAWAN UNIVERSITAS LANCANG KUNING - yandra, alexsander; febriadi, bayu; zamzami, zamzami (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2018)
Computer-based information is very influential in the world of work, as well as web-based information systems are used as a means of information enhancement. Utilization will facilitate a job as well as data processing faster, the decision will be taken more precisely, saving time and cost. In addition, web-based information systems can also be an efficient means of promotion and information resources that can be accessed by Internet users who are increasingly widespread. In the Faculty of Computer Science, the absence of media as a means of gathering RPKPS while the application of the computer and internet and resources already exist, so difficult in adjusting diktat subjects given lecturers against the competence of the study program and for the development of the competence of the study program